Management and Outcome of Transepiphyseal Femoral Neck Fracture-Dislocation with a Transverse Posterior Wall Acetabular Fracture: A Case Report. Issue 3 (July 2018) - Shaath, M. Kareem; Shah, Harsh; Adams, Mark R.; Sirkin, Michael S.; Reilly, Mark C.
Abstract : Case: We present the case of a 10-year-old girl who sustained a transepiphyseal femoral neck fracture with posterior dislocation of the femoral epiphysis and an associated transverse posterior wall acetabular fracture, leading to complete separation of the capital femoral epiphysis. She underwent urgent operative intervention; she was followed for 13 years and achieved an excellent outcome. Conclusion: Pediatric hip fracture-dislocations are complex injuries that should be managed by a competent pelvic reconstructive surgeon in a well-resuscitated patient. If a quality reduction is obtained in a timely manner, the patient has the best chance of achieving a favorable long-term outcome.